Negative Symptoms and the Formation of Social Affiliative Bonds in Schizophrenia - McCarthy, Julie M. (Schizophr Res, 2017)
Negative symptoms in schizophrenia are characterized by deficits in normative experiences and expression of emotion, and they are associated with poor social functioning. Negative symptoms relating to deficits in motivation and pleasure may hinder the development of affiliative bonds. The current study used a novel procedure to examine the relation between negative symptoms and the development of social affiliation within a laboratory setting. Fifty-five men (35 controls; 20 with a schizophrenia spectrum disorder) completed three social affiliation enhancement tasks with an experimenter partner. Self-reported affiliation and affect ratings were assessed before and after the affiliative interaction. Across groups, social affiliation and positive affect increased following the interactive tasks. However, the schizophrenia group reported less positive and more negative affect than controls. Within individuals with schizophrenia, negative symptoms reflecting motivation and pleasure deficits and self-reported social anhedonia were associated with less affiliative feelings of interpersonal closeness and less willingness to interact. Additionally, these self-reported reactions to the interaction partner were significantly related to social functioning in the community. These findings indicate that though individuals with schizophrenia can form affiliative bonds, the extent to which this is possible may be limited by negative symptoms relating to motivation and pleasure. Additional research will be necessary to examine just how these negative symptoms interfere with social affiliation.